Pre & Post-Merger Financial Performance: An Indian Perspective - Ritesh Patel (Journal of Central Banking Theory and Practice, 2018)
The paper compares the before and after merger position of long term profitability with respect to selected Indian banks for a period of 2003-04 to 2013-2014. The financial performance is evaluated on the basis of various variables. The study found a negative impact of merger on return on equity, return on assets, Net profit ratio, yield on advance and yield on investment. However, variables, namely, the Earnings per Share, Profit per employee and Business per employee have shown positive trend and grown after the merger. It has been observed that after the merger, the Assets, Equity, Investment and advances of all banks increases, but due to underutilization, their respective yield decreases. On a contrary, the business per employee and profit per employee have increased due to optimum utilization of human resources. By applying the Comparative Analysis, the paper also assesses the financial performance of acquiring bank with the banking industry. The Bank of Baroda and Oriental bank of commerce has found decreases in Yield on Advances and yield on investment as compared to average of all banks in the post-merger period. State bank of India & IDBI Bank has higher business per employee and profit per employee as compared to industry average.
Keywords: G21; G34; 330; Merger; Financial performance; Bank; India.